Partikül Madde (PM10) Konsantrasyonunun Kentsel Yeşil Alan Sisteminin Değerlendirilmesinde Ekolojik İndikatör Olarak Kullanımı: İstanbul - Beşiktaş Örneği - Batur, Ahmet; Aksu, Gül Aslı (European Journal of Science and Technology, 2021)
Rapid population growth and indirectly increasing unplanned urbanization negatively affect the ecosystem on urban green areas, especially public health and biological diversity. To understand the impact of vegetation structures on local air quality, different design scenarios should be evaluated and simulations are used for design optimization. For this purpose, Beşiktaş district was chosen as it has different landscape elements and a dense population. Before the study, PM10 concentration values of the Istanbul Metropolitan Municipality Environmental Protection Directorate Beşiktaş District Measurement Station between 1998-2019 were reviewed, a preliminary research was carried out by preparing annual graphs to represent monthly averages. It was observed that the PM10 concentration reached its highest values in February and April. Twenty-three measurement points were determined to represent different types of greenway in a homogeneous distribution in the research area. Measurements were made at the planned measurement points with DUSTTRAK II and QUEST EVM 7 devices. According to On-Site Measurement Findings; areas with high PM10 levels; Mustafa Kemal Cultural Center (Gx̄ = 0,107 mg/m3), Barbaros Park (Gx̄ = 0,096 mg/m3), Gültekin Park (Gx̄ = 0,092 mg/m3), while the lowest PM10 levels are; Garanti BBVA (Gx̄ = 0,046 mg/m3) and Ulus Park (Gx̄ = 0,041 mg/m3) were observed. According to the results obtained in the research; urban green areas, especially groves, have a significant effect on PM. It has also been observed that the green texture is important for environmental buildings and parks. The components of green tissue (biomass, high woody mixed nature) is thought to affect PM levels. In addition, possible damages of the vegetation system in the form of unconnected or disconnected units were prevented by the green roof systems in these regions.

Hızlı nüfus artışı ve dolaylı olarak artan plansız kentleşme, kentsel yeşil alanlar üzerinde başta halk sağlığı ve biyolojik çeşitlilik olmak üzere ekosistemi olumsuz etkilemektedir. Bitki örtüsü yapılarının yerel hava kalitesi üzerindeki etkisini anlamak için farklı tasarım senaryoları değerlendirilmeli ve tasarım optimizasyonu için simülasyonlar kullanılmaktadır. Bu amaçla, farklı peyjaz unsurlarına ve yoğun bir nüfusa sahip olduğu için Beşiktaş ilçesi seçilmiştir. Çalışma öncesinde, İstanbul Büyükşehir Belediyesi Çevre Koruma Müdürlüğü Beşiktaş İlçe Ölçüm İstasyonu’na ait 1998-2019 yılları arası PM10 konsantrasyon değerleri gözden geçirilmiş, aylık ortalamaları temsil edecek şekilde yıllık grafikler hazırlanarak ön araştırma gerçekleştirilmiştir. PM10 yoğunluğu Şubat ve Nisan aylarında en yüksek değerlere ulaştığı görülmüştür. Araştırma alanında homojen bir dağılım gösterecek şekilde, farklı tip yeşil alanları temsil edecek 23 adet ölçüm noktası belirlendi. DUSTTRAK II ve QUEST EVM 7 cihazları ile planlanan ölçüm noktalarında ölçümler yapıldı. Yerinde Ölçüm Bulgularına göre; PM10 ölçümlerinde hava kalitesi indeks sınırlarına göre hassas düzeyi aşan bir düzey tespit edilmemiştir. 100-150 µg/m3 hassas düzeyde belirlenmiş; Mustafa Kemal Kültür Merkezi (Gx̄=0,107 mg/m3), Barbaros Parkı (Gx̄=0,092 mg/m3), Gültekin Parkı (Gx̄=0,092 mg/m3), en düşük PM10 düzeylerinin ise; Garanti BBVA (Gx̄=0,046 mg/m3) ve Ulus Parkı (Gx̄=0,041 mg/m3) olduğu görüldü. Sonuç olarak; korular başta olmak üzere kentsel yeşil alanların PM üzerinde anlamlı düzeyde etkisi olduğu, yeşil dokunun çevresel yapılar ve özellikle parklar için önemli olduğu görülmüştür. Yeşil dokunun niteliği PM seviyelerini etkilediği düşünülmektedir. Ayrıca, kopuk üniteler halinde bir vejetasyon sisteminin olası hasarları bu bölgelerdeki yeşil çatı sistemleri ile engellendiği görülmüştür.
Keywords: Engineering; Hava kirliliği; Kentsel Yeşil Alan Sistemi; Kent Ekosistemi; Partikül madde (PM10); Mühendislik; Air pollution; Urban green system; Urban ecosystem; Particulate matter (PM10); 13. Climate action; 11. Sustainability; 15. Life on land